2002
DOI: 10.1136/thorax.57.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Home based neuromuscular electrical stimulation as a new rehabilitative strategy for severely disabled patients with chronic obstructive pulmonary disease (COPD)

Abstract: Background: Passive training of specific locomotor muscle groups by means of neuromuscular electrical stimulation (NMES) might be better tolerated than whole body exercise in patients with severe chronic obstructive pulmonary disease (COPD). It was hypothesised that this novel strategy would be particularly effective in improving functional impairment and the consequent disability which characterises patients with end stage COPD. Methods: Fifteen patients with advanced COPD (nine men) were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
220
3
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(241 citation statements)
references
References 26 publications
9
220
3
9
Order By: Relevance
“…In a randomised controlled double-blind trial of NMES of the quadriceps and calf muscles in stable outpatients with severe COPD, poor baseline exercise tolerance and low ventilatory reserve, NMES led to a significant improvement in maximum quadriceps and hamstring strength, an increase in incremental shuttle walking test distance and reductions in dyspnoea, compared with a sham-treated group [31]. NEDER et al [30] randomised severely breathless COPD patients to either 6 weeks of NMES of the leg muscles or a 6-week control (no NMES) period before undergoing NMES. NMES induced significant improvements in maximal isokinetic strength, a reduction in muscle fatigue and an increase in exercise capacity with improved exercise-related dyspnoea.…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a randomised controlled double-blind trial of NMES of the quadriceps and calf muscles in stable outpatients with severe COPD, poor baseline exercise tolerance and low ventilatory reserve, NMES led to a significant improvement in maximum quadriceps and hamstring strength, an increase in incremental shuttle walking test distance and reductions in dyspnoea, compared with a sham-treated group [31]. NEDER et al [30] randomised severely breathless COPD patients to either 6 weeks of NMES of the leg muscles or a 6-week control (no NMES) period before undergoing NMES. NMES induced significant improvements in maximal isokinetic strength, a reduction in muscle fatigue and an increase in exercise capacity with improved exercise-related dyspnoea.…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…Small controlled studies with this technique in severe and even bed-bound COPD patients have been reported [29][30][31][32][33][34][35]. NMES must be delivered according to specific protocols of intensity, frequency, duration and waveform of the stimulus in order to target optimal muscle response.…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Durmus et al (2007) found an increase of functional performance, as measured by the WOMAC index, in a group of 50 women (aged 42-75 years) suffering from knee osteoarthritis undergoing quadriceps electrical stimulation. Neder et al (2002) showed an increased distance covered in the walking test and some improvement in the cardiopulmonary parameters in a group of 15 elderly subjects (6 females) with chronic obstructive pulmonary disease after a 6-week ES training program of lower limbs. These improvements were considered to be the result of muscle strengthening and local capillary density increase.…”
Section: Discussionmentioning
confidence: 99%
“…after surgery, or in subjects who are not familiar with active, voluntary exercise (Mysiw and Jackson, 2000). Finally, ES was recently shown to be an effective rehabilitative approach in patients with complex pathologies, such as chronic obstructive pulmonary disease (Neder et al, 2002) and congestive heart failure (Quittan et al, 2001). In these conditions the purpose of ES is not only to increase muscle strength, but also to reduce effort during daily activity and to consequently improve self-sufficiency.…”
Section: Introductionmentioning
confidence: 99%